CRF1 receptor activation increases the response of neurons in the basolateral nucleus of the amygdala to afferent stimulation - Ugolini, Annarosa; Sokal, David; Arban, Roberto; Large, Charles H. (Frontiers in Behavioral Neuroscience, 2008)
The basolateral nucleus (BLA) of the amygdala contributes to the consolidation of memories for emotional or stressful events. The nucleus contains a high density of CRF1 receptors that are activated by corticotropin-releasing factor (CRF). Modulation of the excitability of neurons in the BLA by CRF may regulate the immediate response to stressful events and the formation of associated memories. In the present study, CRF was found to increase the amplitude of field potentials recorded in the BLA following excitatory afferent stimulation, in vitro. The increase was mediated by CRF1 receptors, since it could be blocked by the selective, non-peptide antagonists, NBI30775 and NBI35583, but not by the CRF2-selective antagonist, astressin 2B. Furthermore, the CRF2-selective agonist, urocortin II had no effect on field potential amplitude. The increase induced by CRF was long-lasting, could not be reversed by subsequent administration of NBI35583, and required the activation of protein kinase C. This effect of CRF in the BLA may be important for increasing the salience of aversive stimuli under stressful conditions, and for enhancing the consolidation of associated memories. The results provide further justification for studying the efficacy of selective antagonists of the CRF1 receptor to reduce memory formation linked to emotional or traumatic events, and suggest that these compounds might be useful as prophylactic treatment for stress-related illness such as post-traumatic stress disorder.